Penyakit Tuberkulosis di Puskesmas Dosay Sentani Barat Kabupaten Jayapura Tahun 2017-2019 - Asrianto; Fachruddin; Indra Taufik Sahli (Puslitbang Sinergis Asa Professional, 2020)
Papua Province is one of the regions with the highest tuberculosis cases in Indonesia. Especially in the Dosay Health Center's working area, in 2017 found 34 cases, 24 cases in 2018, and 32 cases in 2019. This study aimed to determine the number of cases of TB at the Dosay Public Health Center in 2017-2019, based on gender, age, location of TB anatomy, and place of residence. This study is a quantitative descriptive study. The data source was collected from the Tb case examination's medical record and then analyzed with a descriptive statistic. The results showed that in 2017 and 2018, TB patients tended to be more dominated by women, namely (59.3%) and (70.8%), respectively. While in 2019, the number of men with TB was (61.7%). The highest number of TB sufferers in 2017 was in the age group 25-34 years, namely (37.5%). Meanwhile, the 0-14-year age group was the highest in 2018 and 2019, namely (33.3%) and (47%). The number of pulmonary tuberculosis cases in 2017-2019 was higher than extrapulmonary tuberculosis. TB cases in 2017 were found mostly in Waibron Village and Maribu Village, namely (31.2%) and (28.8%). In 2018 Maribu Village had the highest, followed by Waibron Village, respectively (41.6%) and (29.1%). As for 2019, the most TB patients were found in Sabron Yaru Village with (32.3%). In conclusion, in 2017 and 2018, there were more female TB cases. While in 2019, the highest TB cases were in men. TB cases in 2017-2019 are mostly found in the age group <15 years. The anatomical location most commonly attacked by TB is the lungs. The areas with relatively high TB cases were Waibron, Maribu, and Sabron Yaru Village.